Molecular Dynamics Simulation on Dielectric Constant and Thermal Conductivity of Crosslink Epoxy/functionalized graphene Nano-composites. Issue 1 (February 2020) - Shen, L; Zou, L; Ding, M; Zhao, T; Zhang, L; Li, Q
Abstract: Nanoscale graphene fillers are expected to enhance electronic and thermal properties of polymers owing to the superior performances of graphene. In this paper, dielectric constant and thermal conductivity of crosslink epoxy/functionalized graphene nano-composites were investigated using molecular dynamics simulations. The results show that graphene nanoplatelets (GN) can improve performances of polymer matrix, covalent functional groups can further enhance this improvement. Among different functional groups, hydroxyl is more effective than carboxyl and amino in reducing dielectric constant. Correspondingly, the introduction of graphene fillers also leads to an increase in thermal conductivity. GN and amino functionalized GN raise thermal conductivity of crosslink epoxy by 30.69% and 44.86% respectively. All the results demonstrate that functionalization of GN can suppress polarization and enhance thermal transportation.